Politics, Social Theory, Utopia and the World-System - el-Ojeili, C. author. aut Link
VII, 237 p.
Keywords: It is common to hear that we live in unique, turbulent and crisis-ridden times and this turbulence, transformation and crisis are said to be deeply significant - perhaps threatening - for the human sciences. Responding to such claims, this book provides an accessible engagement with pressing contemporary topics, such as violence, social movements, equality, identity and democracy. Foregrounding the imagination of possibilities (utopia), the mapping of the present (theory), and the transformation of the world-system (historical and global questions), the book surveys central issues and paradigms in contemproary political sociology, urging a recommitment to certain concepts and traditions for guidance in thinking and acting in the world.